Eficiencia de conservación del área regional comunal Tamshiyacu Tahuayo mediante un análisis de inhibición de deforestación del 2009-2023. Loreto 2024 - Llerena Villa, Antony Cristian (2024)
The study analyzes the variation of vegetation cover in the Tamshiyacu Tahuayo Regional Conservation Area (RCA) between 2009 and 2022, with an analysis approach of inhibiting deforestation due to human activities in the different management zones within the protected area. To determine conservation efficiency, spatial data from the National Forest Conservation Program for the Mitigation of Climate Change (PNCBMCC), GEOBOSQUES platform, were used throughout the evaluated period. A significant increase in deforestation was observed, with a total loss of 137.87 hectares of forest cover, despite the protected status of the area. Areas for tourist and recreational use were the most affected, followed by wild areas and direct use. These results indicate that proximity to watersheds and accessibility are key factors that facilitate human intervention in these areas. Additionally, a temporary reduction in deforestation was identified during 2020, attributed to the mobility restrictions imposed by the COVID-19 pandemic. The study concludes that current conservation measures in the Tamshiyacu Tahuayo ACR are not sufficient to mitigate anthropogenic pressure, and suggests the need to strengthen surveillance, review and improve conservation policies, promote sustainable economic activities, and continue research long term to monitor changes in the ecosystem.